Emerging challenges in pharmacotherapy research on attention-deficit hyperactivity disorder: outcome measures beyond symptom control and clinical trials - Wong, Ian Chi Kei; Banaschewski, Tobias (The lancet. Psychiatry, 2019)
Summary - Although pharmacological therapies are recommended as a key component in the treatment of attention-deficit hyperactivity disorder, their use continues to prompt intense debate. Despite considerable research efforts, several gaps in the knowledge base and several questions over the quality of evidence exist. Particular issues surrounding pharmacological treatments include uncertainties about long-term effectiveness and safety, safety profiles in adults, and the comparative effectiveness of different medications. In this Review, we focus on four key methodological issues for future research: (1) the use of appropriate trial designs; the need for (2) outcome measures targeting effectiveness beyond symptom control and (3) safety outcome measures; and (4) the application of clinical and administrative research databases to assess real-world outcomes. Potential solutions include increased use of randomised placebo-controlled withdrawal trials and large pharmacoepidemiological studies that use electronic health-care records on the long-term effectiveness and safety of medications. Pragmatic head-to-head randomised trials would also provide direct evidence on comparative effectiveness and safety profiles.